PENERAPAN MODEL PEMBELAJARAN BERBASIS PROYEK UNTUK MENINGKATKAN KREATIVITAS DAN PRESTASI BELAJAR - Maria Ulfa (UNIB Press, 2024)
The objectives of this study are to: (1) Describe the application of the project based learning model in improve students creativity, (2) Describe science learning through a project based learning model, and (3) Describe the effectiveness of the application of a project based learning model to improve the learning achievement of grade VI students at SD Negeri Gugus 1 Selagan Raya. In this study using the Class Action Research (CAR) method and continued with Experimental Research. The data collection techniques used are (1) observation technique, which is used to obtain qualitative data, namely data about the process of implementing project based learning models during the process of learning activities and (2) test technique, which is used to obtain student achievement data for each each cycle in the form of Pre-test and Post-Test .While the data analysis used in the assessment of student tests are: (1) Observational Data Analysis, (2) Learning Achievement Data Analysis, (3) Quasi Experimental Data Analysis with t-test. The conclusions of this study are: (1) The application of project based learning models can increase students creativity in science subjects, (2) The application of project based learning models can improve student achievement in science subjects at SD Negeri Gugus 1 Selagan Raya in the 2022/2023, and (3) The application of project based learning models can improve student achievement compared to conventional learning models